CREATING EMPLOYEE CREATIVITY IN THE DISRUPTIVE ERA: THE IMPLEMENTATION OF WOMEN SERVANT LEADERSHIP - Ferawati Budiargo; Roy Setiawan (Jurnal Cakrawala Ilmiah, 2023)
Servant leadership is an alternative solution for leadership in a disruptive era. The purpose of this study is to describe the effect of women servant leadership on employee creativity through organizational trust. The novelty contribution to this research is the synthesis of the concept of woman Servant leadership. The sample population of this study is 90 employees in the food and beverage business in Indonesia. This study uses the SEM Path Analysis approach. The results showed that women Servant leadership had a significant and positive influence on employee creativity and organizational trust; meanwhile, organizational trust also has a significant and positive impact on employee creativity; however organizational trust cannot be a mediator variable for women Servant leadership.